The Pemasangan Alat Kontrol Kelembaban Pada Usaha Budidaya Tanaman Anggrek Skala Kecil - Sungkono, Sungkono; Nugrahanto, Nugrahanto; Putera, Zulmy Faqihuddin (Dharma: Jurnal Pengabdian Masyarakat, 2022)
The installation of this equipment can help control the humidity process for orchid cultivation in small-scale greenhouses by entering the humidity values ​​that have been determined, with values ​​of  60%, 70%, and 80%. After that, it is processed by the ESP32 as the controller center, then the LCD (Liquid Crystal Display) will show the current humidity display, then the sensor (SHT11) will read the humidity value if the humidity setpoint is below a predetermined value then the motor is on and the nozzle is working, humidity has reached the desired setpoint then the motor will turn off and the nozzle will stop. The goal to be achieved is to maintain the humidity of orchids in the greenhouse so that it remains stable according to standards and regulations, because in this greenhouse,  to maintain plant humidity is a very crucial thing for orchid cultivation because at the time it was still using human power manually with a water hose. We developed this tool to keep the humidity steady by using a nozzle that makes it a mist of water. By using a system that runs automatically, making it easier for business actors to use this tool and has time efficiency. In its installation, the tool is able to generate humidity through the nozzle using a reference to increase the hysteresis value in the control circuit and get an output that oscillates in the setting point area so that the humidity rises according to the setting point, this is because the water misting process in the test conditions cannot be immediately lost, thus affecting the test results